Gut Microbiota in Chronic Kidney Disease: A Narrative Literature Review - Abdillah, Novandra; Zulklhair Ali; Novadian; Ian Effendi; Suprapti; Elfiani; Rery TF Yuniarti (HM Publisher, 2024)
Chronic kidney disease (CKD) is a growing public health problem related to loss of kidney function and cardiovascular disease as the main causes of morbidity and mortality in CKD. It is known that CKD is associated with intestinal dysbiosis. There is an influence of the gut microbiota on the gut-kidney axis and it works reciprocally: on the one hand, CKD significantly changes the composition and function of the gut microbiota. On the other hand, gut microbiota is able to manipulate the processes that cause the emergence and progression of CKD through inflammatory, endocrine and neurological pathways. Understanding the complex interactions between gut and kidney microbiota may provide novel nephroprotective interventions to prevent the progression of CKD by therapeutically targeting balance of gut microbiota composition.